(untitled) (Third Sector Social Economic Review, 2021)
Renewable energy sources have an important role in dealing global warming and energy security problems of countries. Therefore, the countries support renewable energy sources in their energy production and increase the diversity of energy sources. Solar energy, one of the renewable energy sources, is more accessible and causes less pollution compared to other energy sources. In this context, it is very important to evaluate solar energy investments economically. In this study, the method of discounted cash flow has been used to evaluate economic viability of a hypothetical large scale photovoltaic investment in Turkey. The results of the discounted cash flows method demonstrate that the investment is economically viable when it is supported by the government incentive, but is not viable when it is not supported by any policy mechanism of government. As a result of the Monte Carlo simulation, the probability of the net present value of the investment being positive was determined as 64.1% in case of incentive, and 30.1% in the lack of incentive.